1995
DOI: 10.1016/s0022-5223(95)70394-2
|View full text |Cite
|
Sign up to set email alerts
|

Renal replacement therapy after repair of congenital heart disease in children

Abstract: The development of renal failure necessitating peritoneal dialysis after cardiac operations is associated with a reported mortality greater than 50%. Improved fluid removal and nutritional support have been reported with the use of continuous arteriovenous hemofiltration and continuous venovenous hemofiltration techniques. We have compared our experience with all three techniques in managing children who required renal replacement therapy after cardiac operations in terms of efficacy (fluid removal, calorie in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
54
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 27 publications
9
54
0
3
Order By: Relevance
“…The mortality rate in children with acute renal failure following heart surgery has been reported ranging from 10% to 90% [1][2][3][4][5][6]10,12,20 , and our data confirm these values. This prognosis has been most determined by the underlying disease, intercurrent infections, and hemodynamic changes than by the dialytic method employed.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The mortality rate in children with acute renal failure following heart surgery has been reported ranging from 10% to 90% [1][2][3][4][5][6]10,12,20 , and our data confirm these values. This prognosis has been most determined by the underlying disease, intercurrent infections, and hemodynamic changes than by the dialytic method employed.…”
Section: Discussionsupporting
confidence: 87%
“…Several authors have reported that peritoneal dialysis may not be effective in removing fluids or nitrogen debris in hypercatabolic patients and also that the competence of the peritoneal membrane may be impaired in patients in shock 10 . These facts may be challenged either by clinical demonstration of this or by other studies 1,2,4,6,14 , or by data showing that in patients in shock peritoneal blood perfusion is not reduced enough to impair the efficacy of dialysis 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, there have been improvements in dialysate solutions with the use of low glucose degradation products (GDP), bicarbonate-buffered solutions which are asso-, bicarbonate-buffered solutions which are associated with reduced inflow pain; unfortunately, these solutions are not available in many countries. (68,(77)(78)(79). However, in 1 study, CVVH was associated with better fluid control and was superior to PD in the management of hypercatabolic AKI due to sepsis (79).…”
Section: Pediatric Guidelinesmentioning
confidence: 99%